Influence Of Price And Trust On Consumer Interest In Using Travel Services For Hajj And Umrah At PT. Anugerah Quba Mandiri (A Study On The Community Of Tanah Tinggi Village, Padang Jaya Subdistrict) - Yanti, Atika Norma; Asnaini, Asnaini; Muttaqin, Fasial (LPPJPHKI Universitas Dehasen Bengkulu, 2024)
This study aims to explore the influence of price and trust on consumer interest in using the travel services of PT. Anugerah Quba Mandiri for Hajj and Umrah pilgrimages. A quantitative method was employed, collecting data through surveys from 69 respondents, who were potential or actual customers. A structured survey instrument was utilized to measure respondents' perceptions regarding price, trust, and consumer interest. The collected data were analyzed using multiple linear regression analysis to evaluate the relationship between price and trust with consumer interest. Additionally, validity and reliability tests were conducted to ensure the authenticity and dependability of the research instrument. The research findings indicate that price significantly influences consumer interest in utilizing the travel services of PT. Anugerah Quba Mandiri (t = 7.266, p < .001). However, trust does not show a significant influence (t = -0.293, p = .770.